193k views
5 votes
Let x(t)=e⁻ᵃᵗu(t). Compute its Fourier transform. Based on this result, using Fourier transform properties, determine the Fourier transform for the following signals: v(t)=x(5t−4);

User Mike Dg
by
8.2k points

1 Answer

3 votes

Final answer:

The Fourier transform of x(t)=e^{-at}u(t) is computed first, resulting in X(f) = 1/(a + 2πif). Then, applying time-scaling and shift properties of the Fourier transform, the transform for v(t)=x(5t-4) is found to be V(f) = (1/(5a + 2πif))e^{-2πif(4)}.

Step-by-step explanation:

To compute the Fourier transform of x(t)=e⁻ảtu(t), where u(t) is the unit step function and a is a positive constant, we use the integral definition of the Fourier transform:

\(X(f) = \int_{-\infty}^{\infty} e⁻ảtu(t)e⁻²2πift dt\).

Since the unit step function u(t) is 0 for t < 0, we start the integral from 0:

\(X(f) = \int_{0}^{\infty} e⁻ảte⁻²2πift dt\).

Solving this integral yields the Fourier transform of x(t):

\(X(f) = \frac{1}{a + 2πif}\).

Next, to determine the Fourier transform for the signal v(t)=x(5t−4) using Fourier transform properties, we apply the time-scaling property, which states that a scaling of the time variable by a factor A corresponds to a scaling of the frequency axis by 1/A. In this case, the scaling factor is 5. Additionally, due to the time shift by 4, we apply a phase shift in the Fourier domain. Applying these properties results in:

\(V(f) = \frac{1}{5}X\left(\frac{f}{5}\right)e⁻²2πif(4)\).

Substituting the Fourier transform of x(t) into this expression, we obtain:

\(V(f) = \frac{1}{5}\left(\frac{1}{5a + 2πif}\right)e⁻²2πif(4)\).

\(V(f) = \frac{1}{5a + 2πif}e⁻²2πif(4)\).

User Jan Paolo Go
by
7.5k points